ANALISIS KESALAHAN BERBAHASA PADA PAPAN IKLAN (BILLBOARD) DI TEMBUNG, KABUPATEN DELI SERDANG - Muhammad Fahrul Roji Nasution; Sujinah (STKIP Subang, 2026)
Billboards are a promotional medium widely used by businesses. Billboards serve as a medium for conveying information to the public, but the messages they convey often contain spelling errors. The purpose of this study is to identify the types of language errors found on billboards in Tembung Village, Deli Serdang Regency. The data source for this study was billboards in Tembung Village, Deli Serdang Regency. The method used for data collection was qualitative descriptive analysis. The research instrument was documentation. The techniques used to analyze the data included data reduction, data presentation, and drawing conclusions. The results of this study reveal spelling errors, including the use of letters, punctuation, word spelling, and loanwords in the text on billboards in Tembung Village, Deli Serdang Regency.